2023
DOI: 10.1007/s10555-023-10117-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids in cancer pathogenesis

Abstract: Cancer is a multi-step process that can be viewed as a cellular and immunological shift away from homeostasis in response to selected infectious agents, mutations, diet, and environmental carcinogens. Homeostasis, which contributes importantly to the definition of “health,” is maintained, in part by the production of short-chain fatty acids (SCFAs), which are metabolites of specific gut bacteria. Alteration in the composition of gut bacteria, or dysbiosis, is often a major risk factor for some two dozen tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 187 publications
0
8
0
Order By: Relevance
“…The observed increase in the expression of the stem cell marker expression CD90 in our experiments could potentially result from the reprogramming of SB-induced senescent cells into a stem-cell-like phenotype, which might help overcome and survive the external stress from SB treatment. A previous study highlighted an involvement of SCFA in blockade of cancer stem cell proliferation by altering the gene expression in the Wnt-ß-catenin pathway ( 41 ). Additional research is required to elucidate the precise mechanism and potential involvement of SB’s HDAC-inhibition in the upregulation of CD90 and the remaining effects of the increased stem cell population on cancer survival and progression.…”
Section: Discussionmentioning
confidence: 99%
“…The observed increase in the expression of the stem cell marker expression CD90 in our experiments could potentially result from the reprogramming of SB-induced senescent cells into a stem-cell-like phenotype, which might help overcome and survive the external stress from SB treatment. A previous study highlighted an involvement of SCFA in blockade of cancer stem cell proliferation by altering the gene expression in the Wnt-ß-catenin pathway ( 41 ). Additional research is required to elucidate the precise mechanism and potential involvement of SB’s HDAC-inhibition in the upregulation of CD90 and the remaining effects of the increased stem cell population on cancer survival and progression.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs have been shown to possess antitumor capabilities ( 40 ). However, SCFAs may also promote tumor progression and metastasis via immunomodulatory effects, signal transduction regulation and inflammation modulation, all of which can remodel the TME.…”
Section: Microbial Metabolites Remodel the Tme To Promote Tumor Progr...mentioning
confidence: 99%
“…Indeed, among the many actions of butyrate [ 24 ] (e.g., action on the intestinal barrier, energy production for enterocytes, participation in maintaining glycemic homeostasis, inhibition of histone deacetylase (HDAC)), it also plays a crucial regulatory role in immune system function and, thus, in the immune response to carcinogenic processes. Feitelson et al [ 41 ] suggested that SCFAs, particularly butyrate, can influence gene expression and cancer-associated signaling pathways, promoting cellular differentiation and apoptosis in tumor cells, as well as reducing the inflammation often associated with cancer development. There is now abundant scientific evidence available regarding how disturbances in the intestinal microbiota, particularly affecting the quota of butyrate-producing bacteria, impact both intestinal pathophysiology and the genesis of significant inflammatory effects, contributing to the onset of important pathologies, such as IBD [ 42 ], and the ability to maintain an active and balanced immune response.…”
Section: The Action Of the Microbiota And Butyrate On Immunotherapymentioning
confidence: 99%